1994
DOI: 10.1520/jfs13587j
|View full text |Cite
|
Sign up to set email alerts
|

The Black Soldier Fly Hermetia illucens (Diptera: Stratiomyidae) As a Potential Measure of Human Postmortem Interval: Observations and Case Histories

Abstract: The black soldier fly, Hermetia illucens (L.), has been shown to be a ubiquitous inhabitant of both surface and buried human remains throughout the southern, central and western United States and Hawaii. Unlike most other species of forensically important Diptera, this species frequently dominates bodies in the dry/post decay stage of decomposition. Adults of the black soldier fly appear to initiate oviposition (egg laying) 20 to 30 days postmortem. Even at warm temperatures (27.8°C), subsequent completion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 5 publications
2
55
0
10
Order By: Relevance
“…Similar observations have been made for H.illucens larvae sampled on sheep carrion. The development threshold temperature, reported in literature [12], is of 10 °C; Lord and Pujol-Luz [14] reported that the larvae of H. illucens measure, to its full development, 20-32mm and that to reach this stage, to an average daily temperature of 27.8 °C, requires about 31 days (861.8 ADD) we obtained a minimum interval from death between 01-15 October 2009. The appearance of Dermestes maculatus on decomposing remains of human and other animals makes it a candidate insect to estimate postmortem interval.…”
Section: Volume 4 | Issuementioning
confidence: 56%
“…Similar observations have been made for H.illucens larvae sampled on sheep carrion. The development threshold temperature, reported in literature [12], is of 10 °C; Lord and Pujol-Luz [14] reported that the larvae of H. illucens measure, to its full development, 20-32mm and that to reach this stage, to an average daily temperature of 27.8 °C, requires about 31 days (861.8 ADD) we obtained a minimum interval from death between 01-15 October 2009. The appearance of Dermestes maculatus on decomposing remains of human and other animals makes it a candidate insect to estimate postmortem interval.…”
Section: Volume 4 | Issuementioning
confidence: 56%
“…MonteiroFilho & Penereiro (1987) em estudos com carcaças de Rattus rattus em Campinas, SP, e Moura et al (1997Moura et al ( , 2005 Um outro fato interessante observado durante o experimento é que a exumação dos animais se deu exatamente 120 dias após sua morte. Lord et al (1994) relata que o aparecimento de adultos de H. illucens para oviposição começa a ocorrer de 20 a 30 dias após a morte. Oliveira-Costa (2003) afirma que o tempo total de desenvolvimento dessa espécie é de 50 dias.…”
Section: Resultsunclassified
“…Por serem efetivas em reduzir os nutrientes e modificar a umidade contida no esterco, podem ser utilizadas como ferramenta de valor adicional no controle biológico de certas populações de insetos que se criam nesse substrato (Mariconi et al 1999). Assim como outros estratiomídeos das subfamílias Hermetiinae e Sarginae, H. illucens pode ser classificada como oportunista ou necrófaga secundária (Catts & Haskell 1990;Lord et al 1994).…”
unclassified
See 1 more Smart Citation
“…Indeed, according to the work of Lord et al (1994) and those of Turchetto (2000), Stratiomyidae would be attracted by characteristic odors emitted by the corpse in advanced decomposition phase. When the corpse was completely dried, between the 56th and 63rd post mortem days, adults of Tenebrionidae, Trogiidae and Staphilinidae Coleoptera appeared in very small numbers.…”
Section: Process Of Colonization Of Pig Carcasses By Necrophagous Insmentioning
confidence: 99%